(untitled) (CIPEEX, 2025)
Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD) are two of the main neurodevelopmental disorders listed in the Diagnostic and Statistical Manual of Mental Disorders (DSM-V) and are presented by the guideline as conditions that are often verified simultaneously in individuals. Therefore, this study aims to understand the characteristics shared by both disorders and their impact on individuals with such presentations based on a bibliographic review. The DSM establishes deficits in social communication and interaction and repetitive patterns of behavior as the main diagnoses criteria for ASD, whereas the lack of attention and hyperactivity that interferes with social functioning and development are predominant in ADHD (Associação Psiquiátrica Americana, 2022). However, the manual also highlights the possibility for both presentations to occur as comorbidities, which is supported by research that shows such possibility as varying from 17 to 95% (Antshel, Zhang-James, & Faraone, 2013 apud Chiodi, Fabre, Hashimoto, Lúcio, 2023). Those presentations are linked to neurobiological alterations that are presented in individuals diagnosed with ADHD, such as the insufficiency of pre-frontal cortex and amygdala systems (Couto, Melo-Junior, Gomes, 2010), and other characteristics that are shared by individuals with both conditions, exemplified by the reduction of the activation in frontotemporal regions (Baron-Cohen, 1999 apud Segenheich, Mattos, 2007). When it comes to the behavioral impact of those conditions, the presence of emotional symptoms, conduct problems, hyperactivity, relationship challenges and lack of pro-social tendencies are showed as recurrent both in ASD and ADHD (Chiodi, Fabre, Hashimoto, Lúcio, 2023), with bigger impairment in planning and cognitive flexibility (Geurts et, al, 2004 apud Segenheich, Mattos, 2007) and lack of pro-social behavior in ASD, while more hyperactivity and a reduce verbal intelligence were attributed to ADHD (Chiodi, Fabre, Hashimoto, Lúcio, 2023). Despite those differentiations, Segenheich and Mattos (2007) state the importance of both diagnoses being issued to individuals that meet the specified criteria for the two conditions, as a way of better directing therapeutical strategies to contemplate the wide range of needs they may have. Furthermore, Couto, Melo-Junior and Gomes (2010) reinforce the necessity of clinical observation to be combined with a multidisciplinary evaluation team in order to better understand each case as it is presented. In that way, an enhanced professional approach may contribute to a better view upon each individual specific demands and singularities.